2022
DOI: 10.1371/journal.pone.0277540
|View full text |Cite
|
Sign up to set email alerts
|

Criterion-related validity of Bedriddenness Rank with other established objective scales of ADLs, and Cognitive Function Score with those of cognitive impairment, both are easy-to-use official Japanese scales: A prospective observational study

Abstract: Aim Bedriddenness Rank (BR) and Cognitive Function Score (CFS), issued by the Ministry of Health, Labour and Welfare, Japan, are easy-to-use and widely used in the medical and long-term care insurance systems in Japan. This study aims to clarify the criterion-related validity of the CFS with the Mini-Mental State Examination (MMSE) and ABC Dementia Scale (ABC-DS), and to re-evaluate the criterion-related validity of BR with the Barthel Index (BI) or Katz Index (KI) in more appropriate settings and a larger pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…The well-known Barthel Index, a widely used ADL assessment tool, is time-consuming, 36 whereas the Bedriddenness rank is a convenient ADL scale encompassing various activities, including independence of transferring and eating. 21,22 Therefore, the Bedriddenness rank, which exhibited a strong association with falls in this study, can potentially serve as a valuable predictive factor for falls. Furthermore, this study showed a significant association between falls and male sex.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The well-known Barthel Index, a widely used ADL assessment tool, is time-consuming, 36 whereas the Bedriddenness rank is a convenient ADL scale encompassing various activities, including independence of transferring and eating. 21,22 Therefore, the Bedriddenness rank, which exhibited a strong association with falls in this study, can potentially serve as a valuable predictive factor for falls. Furthermore, this study showed a significant association between falls and male sex.…”
Section: Discussionmentioning
confidence: 70%
“…It demonstrates excellent inter-rater reliability and criterion-related validity, making it a convenient and objective ADL scale. 21 , 22 In a prospective validation study conducted at two acute and chronic care hospitals, the overall area under the curve (AUC) of SFRM2 was 0.793. However, it varied between hospitals, with 0.822 in the acute care hospital and 0.642 in the chronic care hospital, indicating differences in the SFRM2 accuracy between hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…In the assessment, cognitive disability grades were used to categorize applicants' cognitive function into eight levels. These grades have been shown to be strongly correlated with Mini‐Mental State Examination scores 19 . A level II or higher is defined as the onset of dementia 20 .…”
Section: Methodsmentioning
confidence: 99%
“…These grades have been shown to be strongly correlated with Mini-Mental State Examination scores. 19 A level II or higher is defined as the onset of dementia. 20 In the sensitivity analysis for single/three-time-point exposures, the maximum follow-up periods for dementia onset were 9 and 3 years, respectively.…”
Section: Outcome Variablementioning
confidence: 99%